Isolation and characterization of microsatellite loci in the woolly mouse opossum, Micoureus paraguayanus (Marsupialia : Didelphimorphia) - Rodrigues, Fernando P.; Rocha, Flavia S.; Garcia, Jose E.; Garcia, Jose F.; De Vivo, Mario; Matioli, Sergio R. (Blackwell Publishing, 2006)
Five microsatellite loci were isolated and characterized within the woolly mouse opossum (Micoureus paraguayanus), a Neotropical marsupial, using an enrichment cloning procedure. Between four and seven alleles were detected per locus, with expected heterozygosity ranging from 0.358 to 0.560. These microsatellites should provide useful markers in a variety of genetic analyses to examine parentage, inbreeding, population structure and population dynamics in fragmented forest habitats.
Keywords: conservation; enriched library; Marsupialia; microsatellites; Micoureus; opossum